Apresentação - Scliar-Cabral, Leonor; Pinto, Maria da Graça; Zasyekina, Larysa (Signo, 2022)
The special volume of the journal Signo, 88(47), 2022 publishes the submitted, evaluated, accepted and reviewed articles, product of the communications and conferences presented at the Online 12th ISAPL International Congress "New perspectives in psycholinguistic research: language, culture, technologies", June 3-5, 2021.Twenty-two authors represent nine countries (Belgium, Brazil, France, Georgia, Poland, Portugal, Romania, Russia and Ukraine), since, of the seventeen papers selected, some were written by more than one author. Brazilian authors constitute the largest number (eight), which is understandable, since the current ISAPL President and Secretary-Treasurer are Brazilians.